A Guide to Econometrics - Kennedy, Peter (MIT Press, 2012)
In the preface to the third edition of this book I noted that upper-level undergraduate and beginning graduate econometrics students are as likely to learn about this book from their instructor as by word-of-mouth, the phenomenon that made the first edition of this book so successful. Sales of the third edition indicate that this trend has continued - more and more instructors are realizing that students find this book to be of immense value to their understanding of econometrics.